2002
DOI: 10.1016/s0928-8244(01)00305-4
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral and mucosal prime-boost immunization strategies in mice with hepatitis B surface antigen and CpG DNA

Abstract: Synthetic oligodeoxynucleotides (ODN) containing immunostimulatory CpG motifs (CpG ODN) are potent adjuvants to protein antigens administered by parenteral or mucosal routes to BALB/c mice. To date, there have been no studies using combined parenteral/mucosal approaches with CpG DNA as adjuvant. In this study we evaluated different parenteral prime-mucosal boost and mucosal prime-parenteral boost strategies using hepatitis B surface antigen (HBsAg) alone or with different adjuvants: aluminum hydroxide (alum), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…Moreover, this paper investigates the co-administration of CpG ODN 1826, a potent adjuvant in mice that was shown to induce Th1 type immune response in combination with a number of different antigens, such as influenza virus [14], hepatitis B antigen [15][16][17], and tetanus toxoid [18], with the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this paper investigates the co-administration of CpG ODN 1826, a potent adjuvant in mice that was shown to induce Th1 type immune response in combination with a number of different antigens, such as influenza virus [14], hepatitis B antigen [15][16][17], and tetanus toxoid [18], with the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…A number of previous studies have shown the adjuvant activity of CpG DNAs (TLR9 modulators similar to 1 or 3 used in the present study) with HBsAg in mouse models [25][26][27][28][29][30][31][32][33]. CpG DNA has also been used as an adjuvant with HBsAg in early clinical trials [34].…”
Section: Discussionmentioning
confidence: 97%
“…Because of their ability to induce strong Th1 immune responses, CpG DNA compounds have been studied as adjuvants to several vaccines and antigens, including recombinant HBsAg, in preclinical and early clinical studies [25][26][27][28][29][30][31][32][33][34]. In the present study, we investigated the adjuvant activity of CpR-, or R'pG-containing IMOs in a HBsAg immunization model compared with a conventional CpG DNA.…”
Section: Introductionmentioning
confidence: 99%
“…CpG ODN has been shown to be an effective mucosal adjuvant after the administration to different mucosal surfaces such as respiratory tract (73,181,182), the genitourinary tract (183) and the gastrointestinal tract (184,185) in combination with different antigens including the hepatitis B antigen (73,186). Co-administration of CpG ODN with other immunopotentiators or delivery systems has been considered to be useful, especially because of being a strong Th1 profile inducer, which has been shown to be able to dominate the Th2 bias associated with other adjuvants (72,73).…”
Section: Cpg Motifsmentioning
confidence: 99%